2010
DOI: 10.1103/physrevlett.104.195303
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Amplification of Vacuum Fluctuations in a Spinor Condensate

Abstract: Parametric amplification of vacuum fluctuations is crucial in modern quantum optics, enabling the creation of squeezing and entanglement. We demonstrate the parametric amplification of vacuum fluctuations for matter waves using a spinor F = 2 87 Rb condensate. Interatomic interactions lead to correlated pair creation in the mF = ±1 states from an initial unstable mF = 0 condensate, which acts as a vacuum for mF = 0. Although this pair creation from a pure mF = 0 condensate is ideally triggered by vacuum fluctu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
127
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(129 citation statements)
references
References 25 publications
1
127
0
1
Order By: Relevance
“…In particular, observation of coherent spin oscillations have confirmed the mean-field pendulum model for small condensates 4,9,10 . Spin evolution has been previously observed from metastable spin states in many experiments 6,8,[13][14][15][16][17] , however, the experiments have not yet demonstrated spin dynamic in agreement with quantum calculations, except in the perturbative, low-depletion limit at very short times (where a Bogoliubov expansion around the mean field can be used) 12,13,17 , or for conditions where the mean-field approach suffices. Here, we are able to observe quantum spin dynamics that agree well with quantum calculations and demonstrate a rich array of non-Gaussian fluctuations.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…In particular, observation of coherent spin oscillations have confirmed the mean-field pendulum model for small condensates 4,9,10 . Spin evolution has been previously observed from metastable spin states in many experiments 6,8,[13][14][15][16][17] , however, the experiments have not yet demonstrated spin dynamic in agreement with quantum calculations, except in the perturbative, low-depletion limit at very short times (where a Bogoliubov expansion around the mean field can be used) 12,13,17 , or for conditions where the mean-field approach suffices. Here, we are able to observe quantum spin dynamics that agree well with quantum calculations and demonstrate a rich array of non-Gaussian fluctuations.…”
mentioning
confidence: 95%
“…The equilibrium states, domain formation and spin dynamics of spinor condensates have been studied in many experiments [6][7][8][9][10][11][12][13][14][15][16][17] . In particular, observation of coherent spin oscillations have confirmed the mean-field pendulum model for small condensates 4,9,10 .…”
mentioning
confidence: 99%
“…Interestingly, this process resembles parametric down-conversion in optical parametric amplifiers [19]. Indeed, if the m = 0 BEC is unstable after the quench of q, spinchanging collisions lead to an exponential amplification of the population in m = ±1 [20][21][22].…”
Section: -2mentioning
confidence: 97%
“…In that case, spin-changing collisions may lead to correlated Einstein-Podolsky-Rosen (EPR) pairs in m = ±1 [17,18], in a * fdeuretz@itp.uni-hannover.de process which closely resembles parametric down-conversion in nonlinear optics [19]. As a result, spinor condensates may act as parametric amplifiers of matter waves [20][21][22], opening interesting perspectives for the creation of nonclassical states of matter based on spinor BECs. Recently we have shown that the interplay between trapping potential, quadratic Zeeman effect (QZE), and spin-changing collisions crucially determines the amplification gain [21] and its sensitivity with respect to quantum spin fluctuations [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation